ALGORITMA C4.5 DALAM MENGUKUR TINGKAT PENGETAHUAN SISWA TERHADAP PELAJARAN BAHASA INGGRIS - Witulas Ambang Cahyati; Shofa Shofia Hilabi; Agustia Hananto; Tukino Tukino (Jurnal Informatika Kaputama (JIK), 2023)
This study aims to categorize the level of students' knowledge of English lessons. To understand the lesson, the teaching and learning process is certainly very important for a student. Achievement of student knowledge is the main function of the existence of an educator. The large number of vocabulary that often sounds foreign to the ear makes it difficult for students to solve English questions because it is difficult to translate. The data source was obtained from students of class VII (seven) at SMP N 03 West Karawang who filled out an English knowledge questionnaire. The C4.5 algorithm is the classification method that is used, and is assisted by the RapidMiner application. The attributes used are student learning methods, learning tools, teacher teaching methods and student interest and student ambition. The results obtained from this study, the value of gain and entropy attributes obtained 23 English knowledge decision rules where the understanding status totaled 12 rules, the status did not understand totaled 11 rules. The accuracy resulting from classification modeling using the C4.5 Algorithm from RapidMiner is 78.12%. The application of the Algorithm C4.5 classification method can be implemented in order to provide new information related to the concept of students' knowledge of English lessons.